PERANCANGAN MODIFIKASI MESIN BENDING ROTARY BAJA APLIKASI STAND POT BUNGA - Ruzita Sumiati; Yuli Yetri; Fardinal Fardinal; Hamzah Putra (Jurnal Rekayasa Mesin, 2022)
Plants grown in pots continue to grow year after year. A flower pot support or flower pot stand is required to add aesthetic value and save space. The purpose of this research is to develop a steel rotary bending machine design for flower pot stand applications The method used is to calculate the rotational speed of the bending mall, design the transmission, calculate the power and capacity of the machine, calculate and analyze the frame strength, and produce machine design results. The design produces a mall bending rotation of 4.5 rpm with diameters of 100 mm, 120 mm, and 150 mm, an electric motor with a rotation speed of 2840 rpm and a power of 1 HP, 4 pulleys and 2 types A V-belts, a shaft diameter of 20 mm and a 6 x 6 mm key, UCP and UCF type bearings, conical gears with a reduction of 10:16, a gearbox with a reduction of 1:40. The required power is 146 watt (0,2 horsepower), and the engine capacity is 243 bends per hour. The engine frame has dimensions of 750 x 550 x 1000 mm and is made of AISI 1045 material. The highest stress that occurs in the frame is 45.55 N/mm2.